Term birthweight and critical windows of prenatal exposure to average meteorological conditions and meteorological variability - Jakpor, Otana; Chevrier, Cécile; Kloog, Itai; Benmerad, Meriem; Giorgis-Allemand, Lise; Cordier, Sylvaine; Seyve, Emie; Vicedo-Cabrera, Ana Maria; Slama, Rémy; Heude, Barbara; Schwartz, Joel; Lepeule, Johanna (Environment international, 2020)
[Display omitted] •Weather during critical windows in pregnancy may lead to lower term birthweight.•These critical windows appear to differ between male and female infants.•Temperature variability, not just mean temperature, may impact term birthweight.•Even apart from temperature, mean humidity may affect term birthweight. Heat stress during pregnancy may limit fetal growth, with ramifications throughout the life course. However, critical exposure windows are unknown, and effects of meteorological variability have not been investigated. We aimed to identify sensitive windows for the associations of mean and variability of temperature and humidity with term birthweight. We analyzed data from two French mother–child cohorts, EDEN and PELAGIE (n = 4771), recruited in 2002–2006. Temperature exposure was assessed using a satellite-based model with daily 1-km2 resolution, and relative humidity exposure data were obtained from Météo France monitors. Distributed lag models were constructed using weekly means and standard deviation (SD, to quantify variability) from the first 37 gestational weeks. Analyses were then stratified by sex. Results for each exposure were adjusted for the other exposures, gestational age at birth, season and year of conception, cohort and recruitment center, and individual confounders. There was no evidence of association between term birthweight and mean temperature. We identified a critical window in weeks 6–20 for temperature variability (cumulative change in term birthweight of −54.2 g [95% CI: −102, −6] for a 1 °C increase in SD of temperature for each week in that window). Upon stratification by sex of the infant, the relationship remained for boys (weeks 1–21, cumulative change: −125 g [95% CI: −228, −21]). For mean humidity, there was a critical window in weeks 26–37, with a cumulative change of −28 g (95% CI: −49, −7) associated with a 5% increase in humidity for each week. The critical window was longer and had a stronger association in boys (weeks 29–37; −37 g, 95% CI: −63, −11) than girls (week 14; −1.8 g, 95% CI: −3.6, −0.1). Weekly temperature variability and mean humidity during critical exposure windows were associated with decreased term birthweight, especially in boys.